(untitled) (Research, Society and Development, 2021)
Bichectomy surgery has been increasingly widespread and performed as an aesthetic, functional, or aesthetic-functional treatment. This study aims to describe the surgical technique of bichectomy with the application of the Kinesio tape to verify its effectiveness in controlling edema formation, with the measurement in four postoperative periods. Through a split-mouth, double-blind, randomized study, 13 participants who had an indication for the surgery were selected and divided into two groups - Control Group: bichectomy surgery and cryotherapy for a period of 12 hours, without external application of the Kinesio tape (KT) and Experimental Group: bichectomy surgery, cryotherapy for a period of 12 hours, and application of KT in the outer cheek area of the face, for 2 days. A millimeter measuring tape was used to measure three reference points on the face before and after the surgical procedure (preoperative, 24 hours, 48 hours, and 7 days postoperatively). Quantitative data were subjected to statistical analysis using the Sigma Plot 12.0 program (Exakt graphs and data analysis, San Jose, USA). The comparisons were made according to the edema measurements for the two experimental groups (2 levels: Kinesio tape versus cryotherapy) and the periods of analysis (4 levels: Preoperative, 24 hours, 48 hours and 7 days postoperatively). After obtaining the data, and the statistical analysis, the application of Kinesio Tape proved to be more effective when compared to the use of cryotherapy alone, in the control of postoperative edema in patients who underwent bichectomy surgery. The study contributes to the literature regarding the applicability of the KT and expands the therapeutic possibilities in an aesthetic-functional procedure that is increasingly sought after by patients.